Mesoporous Co3O4 and CoO@C topotactically transformed from chrysanthemum-like Co(CO3)0.5(OH)·0.11H2O and their lithium-storage properties - Xiong, Shenglin (2012)
In this work, a novel hydrothermal route is developed to synthesize cobalt carbonate hydroxide, Co(CO3)0.5(OH)·0.11H2O. In this method, sodium chloride salt is utilized to organize single-crystalline nanowires into a chrysanthemum-like hierarchical assembly. The morphological evolution process of this organized product is investigated by examining different reaction intermediates during the synthesis. The growth and thus the final assembly of the Co(CO3)0.5(OH)·0.11H2O can be finely tuned by selecting preparative parameters, such as the molar ratio of the starting chemicals, the additives, the reaction time and the temperature. Using the flower-like Co(CO3)0.5(OH)·0.11H2O as a solid precursor, quasi-single-crystalline mesoporous Co3O4 nanowire arrays are prepared via thermal decomposition in air. Furthermore, carbon can be added onto the spinel oxide by a chemical-vapor-deposition method using acetylene, which leads to the generation of carbon-sheathed CoO nanowire arrays (CoO@C). Through comparing and analyzing the crystal structures, the resultant products and their high crystallinity can be explained by a sequential topotactic transformation of the respective precursors. The electrochemical performances of the typical cobalt oxide products are also evaluated. It is demonstrated that tuning of the surface texture and the pore size of the Co3O4 products is very important in lithium-ion-battery applications. The carbon-decorated CoO nanowire arrays exhibit an excellent cyclic performance with nearly 100% capacity retention in a testing range of 70 cycles. Therefore, this CoO@C nanocomposite can be considered to be an attractive candidate as an anode material for further investigation.